Henry Robinson Luce papers - Luce, Henry Robinson, 1898-1967.
Correspondence (1935-1967); manuscripts of speeches, writings, and unpublished book; legal and financial papers; subject files; honorary degrees, awards, invitations, and citations; and other material relating primarily to Luce's advisory and philanthropic activities and, to a lesser degree, his career, households, finances, and travels. Major topics include the social, cultural, and political history of China, U.S. social and political history, ecology, education, Christianity, philanthropy, civil rights, and international law and are reflected in Luce's association with such organizations as China Institute in America, Council on Foreign Relations, Fifty Million Fund, Institute of Pacific Relations, Laymen's Movement for a Christian World, National Presbyterian Church, National Urban League, Rockefeller Brothers' Fund, United Board for Christian Higher Education in Asia, United China Relief, United Service to China, Yale-In-China Association, and the Luce Professorship of Jurisprudence at Yale Law School.
Correspondents include Raymond E. Baldwin, Lord Beaverbrook, Chester Bowles, Brendan Bracken, Pearl S. Buck, William C. Bullitt, John Foster Dulles, Dwight D. Eisenhower, Lyndon B. Johnson, Walter Henry Judd, Henry Cabot Lodge, Henry Kissinger, Archibald MacLeish, Sir Robert Gordon Menzies, Nelson A. Rockefeller, David O. Selznick, Spyros Panagiotes Skouras, Herbert Bayard Swope, Arthur H. Vandenberg, Thornton Wilder, and Wendell L. Willkie.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Editor, publisher, and philanthropist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baldwin, Raymond E. -- 1893-1986 -- Correspondence; Beaverbrook, Max Aitken, -- Baron, -- 1879-1964 -- Correspondence; Bowles, Chester, -- 1901-1986 -- Correspondence; Bracken, Brendan, -- 1901-1958 -- Correspondence; Buck, Pearl S. -- 1892-1973 -- Correspondence; Bullitt, William C. -- 1891-1967 -- Correspondence; Dulles, John Foster, -- 1888-1959 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Judd, Walter Henry, -- 1898-1994 -- Correspondence; Lodge, Henry Cabot, -- 1902-1985 -- Correspondence; Kissinger, Henry, -- 1923- -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Menzies, Robert, -- 1894-1978 -- Correspondence; Rockefeller, Nelson A. -- 1908-1979 -- Correspondence; Selznick, David O., -- 1902-1965 -- Correspondence; Skouras, Spyros Panagiotes, -- 1893-1971 -- Correspondence; Swope, Herbert Bayard, -- 1882-1958 -- Correspondence; Vandenberg, Arthur H. -- 1884-1951 -- Correspondence; Wilder, Thornton, -- 1897-1975 -- Correspondence; Willkie, Wendell L. -- 1892-1944 -- Correspondence; China Institute in America; Council on Foreign Relations; Institute of Pacific Relations; National Presbyterian Church (Washington, D.C.); National Urban League; Rockefeller Brothers Fund; United Board for Christian Higher Education in Asia; United China Relief (U.S.); United Presbyterian Church in the U.S.A. -- Fifty Million Fund; Yale-in-China Association; Yale Law School; Christianity; Civil rights; Ecology; Education; Endowments; International law; Journalism; Presbyterian Church -- Washington (D.C.); Social history; Social problems; China -- Cultural policy; China -- Politics and government; China -- Social conditions; United Service to China; Editors; Publishers; Philanthropists